Pengaruh Kualitas Produk, Promosi dan Kepercayaan Terhadap Keputusan Pembelian pada Shopee - Dinda Dinda; Sunargo Sunargo (J-MAS (Jurnal Manajemen dan Sains), 2023)
In this era of increasingly rapid development of globalization, it will trigger increasingly high competition in the business world. This high competition in market share will force companies to always innovate, as well as increase their level of creativity, within the goal of increased the levels of purchasing decisions for a product. There are several things that influence and become a reference in the level of purchase decisions, including product quality, promotion, and trust in a product. Where the three have a very close and significant relationship in an aspect of market share. The aim of his researches is to explore the effects of product quality, promotions and trust on purchase decisions at Shopee. With the quantitative method and a total sample of 100 respondents, namely Shopee users in Batam City. formula. Questionnaires are used as a technique in collecting data and the result of that research It was found that product quality, promotion and trust had a positive and significant effect partially or simultaneously on purchase decisions at Shopee. Therefore shopee needs to improve product quality, promotionÂ  and trust in product to improve purchase decision.